اساليب المعاملة الوالدية ومدى تأثيرها على اكتساب السلوك الصحي لدى المراهق المصاب بداء السكري - مصباح, علي (كلية العلوم الاجتماعية, 2020)
Abstact: The present study aims to find out the extent to which the adolescent is affected by the methods of normal parental treatment, and the extent to which he is affected by the methods of abnormal parental treatment. It also aims to know the extent to which healthy behavior is affected by the type of diabetes, and to know the extent to which parental treatment methods are affected by the type of disease that the teenager suffers. Parental treatment methods are considered one of the important determinants of adolescent behavior and affecting his psychological and physical health, depending on the type of parental treatment that he receives from one or both of his parents. A diabetic in the family environment remains what is certain, according to the results of studies in this field, is that the methods of parental treatment have an effect on the acquisition of healthy behavior in the adolescent with diabetes, so that the type of method adopted in parenting treatment, whatever it is, that gives us a reaction by the teenager The diabetic is ultimately affected by the size and severity of this method, In this context, this study came with a set of hypotheses, as follows: General hypothesis: Parental treatment methods affect the acquisition of a healthy behavior in the adolescent with diabetes. Partial hypotheses: 1- Parental treatment methods differ between city and countryside. 2- Healthy behavior is affected by the duration of diabetes. 3- Parents ’educational level affects the achievement of healthy behavior for a diabetic adolescent. 4- The economic and living standards of parents affect the methods of parental treatment adopted in equipping the teenager with healthy behavior. The researcher relied in his study on the clinical approach and case study, and this study was conducted at the Psychological Pedagogical Center for Mentally Handicapped Children in Sidi Ali, and the duration of this procedure extended from 09 February to 05 March 2020, where the specifications of the studied cases were as follows : Adolescents between the ages of 14 and 15 years old, with diabetes, present at the educational psychological center for the mentally handicapped. In the end, the researcher reached a set of results, including that the methods of parental treatment of all kinds affect the acquisition of healthy behavior in the adolescent with diabetes (the methods of normal and abnormal parental treatment) and from the methods present in this study, we find the democratic style, the method of acceptance, the method of tolerance, the method of neglect and rejection, We also find that the methods of parental treatment are affected by a group of variables, including the difference in the place of residence in the city or countryside, and affected by the educational and economic level of the parents.
Keywords: المعاملة الوالدية؛السلوك الصحي؛داء السكري